VALIDITAS PENAFSIRAN DALAM TAFSÃR BI AL-MAâTSÃRVALIDITAS PENAFSIRAN DALAM TAFSÃR BI AL-MAâTSÃRVALIDITAS PENAFSIRAN DALAM TAFSÃR BI AL-MAâTSÃR - Hudaya, Hairul (Fakultas Ushuluddin dan Humaniora IAIN Antasari, 2015)
There are three methods of interpretation used by commentators to interpret the Qurâanic verses, by riwayah, knownÂ as tafsÃ®r bi al-maâtsÃ»r, by logic known as tafsÃ®r bi al-raâyi and by al-isyÃ¢ri. From three methods of interpretation,according to Ibn Taymiyyah, tafsÃ®r bi al-maâtsÃ»r is the best method and valid. It is based on the belief that knows theÂ meaning of the verse is Allah, the Prophet, and his companions. In fact, the commentary by al-maâtsÃ»r, not the wholeÂ verse is interpreted by the Prophet, or friends but the majority carried out by commentators with ijtihadnya in placingÂ the Qurâan, Hadith and friends opinion when interpreting a verse. Thus, differences in interpretation among commentatorsÂ bi al-maâtsÃ»r can not be avoided. In case of Abrahamâs son who was sacrificed, for example, between al-Thabari, Ibn KatsÃ®r and Ibn âAthiyyah had different opinions and attitudes of understanding of the verses. WhileÂ their interpretation is called tafsÃ®r bi al-maâtsÃ»r. Their different opinions indicate that al-tafsÃ®r bi al-maâtsÃ»r also needÂ a review of the validity, especially related to commentatorâs thought in placing the explanation of Qurâan itself,Â Hadith and opinion in interpreting the Qurâanic verses.